Preparation and evaluation of a phospholipid-based injectable gel for the long term delivery of leuprolide acetaterrh - Danhong Long; Tao Gong; Zhirong Zhang; Rui Ding; Yao Fu (Elsevier, 2016)
A phospholipid-based injectable gel was developed for the sustained delivery of leuprolide acetate (LA). The gel system was prepared using biocompatible materials (SPME), including soya phosphatidyl choline (SPC), medium chain triglyceride (MCT) and ethanol. The system displayed a sol state with low viscosity in vitro and underwent in situ gelation in vivo after subcutaneous injection. An in vitro release study was performed using a dialysis setup with different release media containing different percentages of ethanol. The stability of LA in the SPME system was investigated under different temperatures and in the presence of various antioxidants. In vivo studies in male rats were performed to elucidate the pharmacokinetic profiles and pharmacodynamic efficacy. A sustained release of LA for 28 days was observed without obvious initial burst in vivo. The pharmacodynamic study showed that once-a-month injection of LA-loaded SPME (SPME-LA) led to comparable suppression effects on the serum testosterone level as observed in LA solution except for the onset time. These findings demonstrate excellent potential for this novel SPME system as a sustained release delivery system for LA.